Relevance of Pedagogical Practice in Psychological Education - Sayora Rustamovna Kamalova (Scientific Trends, 2026)
This article explores the relevance of pedagogical practice in higher education psychology. Pedagogical practice is viewed not as a formal "clockwork" but as a key mechanism for transitioning from academic knowledge to professional action: working with groups, designing developmental and preventive measures, providing psychological and pedagogical support, and professional communication. It is argued that modern psychologist training requires robust pedagogical competencies, as graduates increasingly work in educational settings, conducting trainings, consultations, and psychoeducation, and participating in teamwork with teachers.
Keywords: Pedagogical practice, psychological education, practical training, competence-based approach, supervision, reflection, psychoeducation, professional ethics.